A Rare Homoisoflavonoid Cambodianol from Sansevieria roxburghiana - Roy, J.; Aktar, F.; Haq, M.R.; Begum, B.; Hasan, C.M. (Asian Journal of Chemistry, 2013)
A homoisoflavonoid and a triterpene were isolated from the carbon tetrachloride soluble fraction of a methanol extract of the whole plants of Sansevieria roxburghiana (Agavaceae). The structures of the isolated compounds were elucidated as cambodianol (1) and lupeol (2) by extensive spectroscopic studies, including high field NMR analyses.